Case report: Pathological complete response to neoadjuvant brigatinib in stage III non-small cell lung cancer with ALK rearrangement - Seong, Hayoung; Kim, Soo Han; Kim, Mi Hyun; Cho, Jeong Su; Kim, Ahrong; Eom, Jung Seop (Frontiers in Oncology, 2024)
Purpose: The use of neoadjuvant anaplastic lymphoma kinase (ALK)-tyrosine kinase inhibitors (TKIs) has not been extensively explored. The current case report highlights the notable pathological complete response (pCR) achieved following neoadjuvant brigatinib therapy in a patient with stage ⅢA ALK-positive non-small cell lung cancer (NSCLC). Case presentation: A 32-year-old male presented with incidental lung lesions, ultimately diagnosed as clinical stage T3N1M0, ⅢA NSCLC with an ALK gene rearrangement. Following a multidisciplinary discussion, the patient opted for neoadjuvant brigatinib therapy, which significantly reduced the tumor size. Subsequently, surgery with curative intent was performed, revealing pCR with no residual tumor cells. The patient remained disease-free during an 8-month follow-up period.This case report provides compelling evidence of pCR following brigatinib therapy in ALK-positive NSCLC, suggesting that surgery after neoadjuvant therapy with brigatinib may offer a safe and effective approach for patients with ALK-positive NSCLC.